Africa RISING-Yield of Maize-Vegetable Intercrop in Northern Ghana - International Institute of Tropical Agriculture; World Vegetable Center; Savanna Agricultural Research Institute; Ministry of Food and Agriculture, Government of Ghana (International Food Policy Research Institute, 2015)
Project title: Africa RISING-Yield of Maize-Vegetable Intercrop as Influenced by Varying Plant Densities in Northern Ghana. Project abstract: The project aims i) to determine the effect of insect/pest and diseases on maize vegetable intercropping and ii) to determine farmer preferences and cost benefit analysis. Project website: http://africa-rising.net http://africa-rising.net/where-we-work/west-africa